PENINGKATAN PENGETAHUAN PENGGUNAAN TEKNOLOGI DALAM MENGHADAPI PELUANG DAN TANTANGAN BAGI PELAKU USAHA UMKM DI DESA SELOMORO, KECAMATAN JENAWI, KABUPATEN KARANGANYAR - Erni Widiastuti; Sarsiti; Asih Handayani (Surakarta Abdimas Journal, 2024)
Abstract The objective of implementing the outreach program in the context of community service activities with the theme "Increasing knowledge of the use of technology in facing opportunities and challenges for MSME business actors" is to empower MSMEs in Selomoro Village, Jenawi District, Karanganyar Regency with the knowledge, skills and support needed to utilize technology in marketing them, so that they can compete more effectively in an increasingly competitive global market. The activity method is carried out using two methods: (a) Presentation (the material presented in community service activities is the marketing challenges faced, the potential use of technology for MSME business actors, and digital market opportunities for MSME business actors; in powerpoint form) (b) Questions and answers and discussion of the results of the implementation of the outreach program provide an opportunity for participants to exchange information and discuss the challenges and solutions they face in facing the digital market. In this session, it is hoped that MSME business actors in Selomoro Village can overcome the challenges they face and take advantage of the opportunities available to improve their overall business performance. By supporting MSMEs in overcoming challenges related to the use of technology in marketing. Keywords: Counseling, Use of Technology, and MSME Business Actors